Chiral gliding: Right-handed navigation of filamentous cyanobacteria - Andrej Vilfan; Leila Abbaspour; Stefano Villa; Vahid Nasirimarekani (Proceedings of the National Academy of Sciences, 2026)
Cyanobacteria are the earliest known organisms that produced oxygen through photosynthesis, leading to the oxygen atmosphere that allowed the evolution of more complex life forms. Many species of cyanobacteria exhibit gliding motility along surfaces to navigate complex environments and adapt to fluctuating conditions. Here, we studied the gliding motility of filamentous cyanobacteria Lyngbya lagerheimii at the transition between different physical environments. We show that on a dry surface, a filament adopts a curved shape that turns right while gliding. When a filament switches the gliding direction, the curvature is initially preserved and a filament can turn left as long as it backtracks along a slime trace. We propose a model of chiral motility that explains the bending based on the right-handed rotation of gliding filaments and a velocity mismatch between the leading and the trailing end of the filament. The mechanism involves a unique way of transferring the structural chirality to the macroscale and also a unique physical navigation mechanism.